2015
DOI: 10.1038/srep08533
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Arcs vs. Fermi Pockets in Electron-doped Perovskite Iridates

Abstract: We report on an angle resolved photoemission (ARPES) study of bulk electron-doped perovskite iridate, (Sr1−xLax)3Ir2O7. Fermi surface pockets are observed with a total electron count in keeping with that expected from La substitution. Depending on the energy and polarization of the incident photons, these pockets show up in the form of disconnected “Fermi arcs”, reminiscent of those reported recently in surface electron-doped Sr2IrO4. Our observed spectral variation is consistent with the coexistence of an ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…For example, the non-superconducting nickelate Eu 0.9 Sr 1.1 NiO 4 exhibits one. 13 It is also worth noting that other groups have measured ARPES on bulk-doped iridates 14 but do not see this Fermi arc phenomenology. So, the jury remains out on the possible connections between Sr 2 IrO 4 electronic structure and that of the cuprates.…”
mentioning
confidence: 99%
“…For example, the non-superconducting nickelate Eu 0.9 Sr 1.1 NiO 4 exhibits one. 13 It is also worth noting that other groups have measured ARPES on bulk-doped iridates 14 but do not see this Fermi arc phenomenology. So, the jury remains out on the possible connections between Sr 2 IrO 4 electronic structure and that of the cuprates.…”
mentioning
confidence: 99%
“…Since minor La dopants have little structural effect on IrO 2 layers while driving the system across the IMT, (Sr 1−x La x ) 3 Ir 2 O 7 provides an ideal platform to exploring novel phenomena arising from charge carrier doped J eff = 1 2 Mott states, in the presence of strong interlayer couplings and pseudodipolar interactions [29,30]. However, the doping evolution of the ground state of (Sr 1−x La x ) 3 Ir 2 O 7 is still under intense debate [32][33][34][35]. Angle-resolved photoemission (ARPES) measurements revealed a strong coherent quasiparticle peak and suggested a weakly correlated Fermi liquid ground state in (Sr 0.95 La 0.05 ) 3 Ir 2 O 7 [33].…”
mentioning
confidence: 99%
“…On the other hand, an angle-resolved photoemission spectroscopy (ARPES) experiment suggested a conventional Fermi-liquid state of (Sr 1 −  x La x ) 3 Ir 2 O 7 with a small mass renormalization of about 219. Band structure calculations also suggested that Sr 3 Ir 2 O 7 might be almost a band insulator19202122. A tight-binding calculation predicted that a direct gap between the bands mainly composed of the J eff  = 1/2 states occurred at every momentum point and the Fermi level was found to barely touch the bottom of the occupied bands and the top of the unoccupied bands.…”
mentioning
confidence: 99%